Conflicts and Mitigation measures Inrwandan protected areas. A case of Volcanoes National Park. - Jean Damascene, Hakizimana (Kabale University, 2020)
This study examined the conflicts in VNP and their mitigation measures; the kind of conflicts that occurred between VNP management and local community, their levels, the mitigation measures put in place by managers of this protected area and involvement of local community in suggestion of effective solutions to the problem. Data were collected through the survey from 94 households, selected by using Stratified Random Sampling method. The results showed that communities living near VNP were being suffered for a long time by animals ranging outside of park without compensation. The surrounding communities prefer micro- compensation from macro-compensation that is given in common by considering revenue sharing as the compensation to their damaged properties. They suggest the full amount of compensation by considering the report evaluation done by the committee and not reduce the amount; to the third or the half of the total amount without any consultation to the responsible of property damage. In this study, communities suggest the fencing of VNP as the sustainable solution for human-wildlife conflict management. Community surrounding VNP are still suffering of property loss due to crops raiding by animals that ranging outside of park and this loss reduce their effective participation in park conservation and lead to unceasing dependence on park’s natural resources for living. The study concluded that the human-wildlife conflicts in VNP is a problem, that ask sufficient efforts from government with involvement of different stakeholders, for decision making with the suggestion of necessarily effective mitigation measures; and recommends the individual involvement in achieving sustainable conservation.